WEB Based Social Assistance Recipient Selection Application Based on Community Education Level With C4.5 Algorithm - Nurdiansah Nurdiansah; Usman; Sitti Harlina; Irmawati (Ceddi Journal of Education, 2022)
The Koramil 1408-02/Tallo office is in charge of distributing social assistance recipients. The social assistance is in the form of basic food assistance for the community and MSMEs for people who have micro-enterprises, where each aid has different criteria in determining the recipient. Regarding the existing social assistance and having different criteria in determining acceptance, including the level of education, of course, the staff of the 1408-02/Tallo Koramil Office will find it difficult to carry out the selection process. Based on existing data mining, beneficiaries can be made to assist beneficiaries who will assist the Koramil 1408-02/Tallo staff. Classification can be done using the C4.5 algorithm. This study aims to determine the recipients of social assistance and apply it in the development of the recipient system of social assistance, including the level of community education. This makes it easier to determine recipients of social assistance and the results of this study are applications for social assistance recipients, so that they can overcome the problems that exist in the current system. Based on the results of the research that has been done on the design of this application, it has succeeded in helping the Koramil Office 1408-02/Tallo in selecting social assistance recipients based on the recipient's education and functioning as expected.